Essays in Development Economics - Mahar, Hamad Sikandar (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
This thesis is a collection of three essays in Development Economics. In 2022, 685 million people globally lived in extreme poverty, the rate of decline in poverty is at a paltry rate of 2 percent per year (World bank, 2023). Many factors contribute to this situation such as global headwinds, ineffective national policies, uneven distribution of growth and restrictive social norms to name a few. This dissertation considers two facets that contribute to our understanding of poverty, social norms (their origins and policies to circumvent them) and the status of households in developing countries. The first essay (Chapter 2), co-authored with Andrea Guariso, Marijike Vertpooten and Elena Briones Alonso studies the relation between long-run disease burden and present-day witchcraft beliefs in sub- Saharan Africa (SSA). Scholars have distinguished several psychological and economic arguments for why a heavy disease burden may promote witchcraft beliefs, but there is little empirical evidence for such a relation. We focus on malaria, which is one of the major diseases in historical and contemporary SSA, and for which we can rely on a measure of ethnicity-level historical malaria mortality. Relating this measure to contemporary witchcraft beliefs across individuals and ethnic groups within 17 SSA countries, we find a statistically significant positive association that is robust to the addition of a large number of individual, regional and ethnicity-level control measures. This result, in combination with a substantial body of anthropological, psychological, economic, and evolutionary literature detailing underlying mechanisms, bolsters the idea that the disease environment played a role in explaining the emergence of witchcraft beliefs in SSA. The second essay (Chapter 3), considers national policies to combat adverse social norms. This paper studies the impact of granting formal legal protection to children on their health by studying the impact of the Child Rights Act in Nigeria. Using a Difference in Differences model that is robust to the staggered adoption of this reform across states, I show that granting formal protection to children leads to a reduction in stunting and has limited positive effects on vaccinations. I provide suggestive evidence that the mechanism behind these results is a change in the demand of care by parents. These findings suggest that secular laws which grant protection improve outcomes for children in a society where harmful traditions persist. The third essay (Chapter 4), studies the impact of changes in cassava prices on household food security. I find that an increase in the price of domestic and imported cassava is negatively associated with household food security measures and the effect varies depending on the wealth classification of a household, at baseline households which are classified as being wealthy are impacted by domestic and imported cassava prices more than poor and medium wealth households as measured by the Household Diversity Score (HDDS), while domestic and imported cassava prices impact the average (medium) wealthy households the most as measured by the share of food expenditure. These empirical results are consistent with the predictions of the theoretical models of Engel and Bennett?s price increase impacts on households. These findings support the idea of hungry farmers in developing countries. The last section (Chapter 5) concludes and discusses the implications of this research.
APPROVED